The Use of Janus Kinase Inhibitors in Axial Spondyloarthritis: Current Insights - Eric Toussirot (MDPI AG, 2022)
Current pharmacological treatments of axial spondyloarthritis (axSpA) are limited to non-steroidal anti-inflammatory drugs (NSAIDs) and biological agents, including TNFα inhibitors and IL-17 inhibitors. Despite the availability of these agents, many patients either fail to respond adequately, lose their initial therapeutic response over time, or develop undesirable side effects, thus highlighting the need for new treatment options. Janus kinase (JAK) and signal transducers and activators of transcription (STAT) are a group of intracellular kinases that play a role in the signaling pathway induced by cytokines and certain growth factors associated with the inflammatory process of axSpA. There are several lines of evidence implicating the JAK-STAT pathway in the pathophysiological process of axSpA, including genetic data, the use of certain JAK in the intracellular signal of specific cytokines involved in axSpA (IL-23, IL-22, and IL-6), and data from experimental models of SpA. This provides a rationale for the assessment of JAK inhibitors (JAKi) in clinical trials with patients with axSpA. In this review, we examine the role of JAK-STAT signaling in the pathogenesis of axSpA and summarize the results from recent clinical trials of JAKi (tofacitinib, upadacitinib, and filgotinib) in patients with axSpA.